Management: The New Workplace - Dorothy Marcic; Richard L. Daft (Canada South-Western Cangage Learning, 2013)
Prepare students for management success with this engaging survey of modern management practice. It seamlessly integrates classic management principles with today's latest management ideas to create a responsive market leading text that captivates today's readers.
Keywords: Management; Work environment; Textbooks; (CSE3005-N) Concepts and Principles of International Management